Neospora Caninum en Bovinos de Leche en Cuatro Sectores del cantón Salcedo- Cotopaxi mediante La Prueba De Eliza. - Samaniego Pazmiño, Kevim Alejandro (2019)
The research of the prevalence of Neospora Caninum in dairy cattle of the Cotopaxi province, in four sectors (Bellavista, Anchilivi, Chilivi Census, Santa Ana) of the Salcedo Canton, for the strict contact it has with canines of the area that may be the carriers of this parasitic disease, 100 blood samples were taken with an amount of 5ml of the coccygeal or jugular vein of milk cattle, then they were taken to the laboratory under adequate temperature conditions (8ºC), in time required for the laboratory, the samples They underwent tests of Neospora Caninum (ELIZA Competitive) in the laboratory (VetLab). The results of the substrate enzyme analysis (Competitive ELIZA) were tabulated and indicate that, 25 animals are positive, 75 negative, representing 25% and 75% of the study population, of the 25 positive all are female, while of the 100 animals performed the Neospora Caninum 7 test are male, all of the negative, which represents 7% of the study population. Of the total number of animals with Neospora Caninum, in the Anchilivi neighborhood, the prevalence percentage that it showed was 28%, representing 7 animals in the sector; while in Censo Anchilivi, with 32% of 8 animals in the sector; Santa Ana with 16% of 4 animals in the sector and Bellavista with 24% of 6 animals in the sector. This parasitic disease is essential in the bovine species; it has more excellent distribution and contagion through contaminated water, food, and dog feces. In several sectors of the Salcedo Canton, there is a high production of milk cattle, where this protozoan causes reproductive problems such as abortion, mummification and uterine infections in cattle and also productive among others, causing economic losses to dairy cattle producers. With the results of the investigation, the owners will take preventive, zoosanitary measures and strict deworming control for dogs in the area of exploitation, such as proper handling of debris from dogs and cattle that contaminated in the herd.